Casting a resource-based view on intangible assets and export behaviour - Nasab, Seyyed Mohammad Tabatabaei; Farhangnejad, Mohammad Ali; Naysary, Babak (Business, Management and Economics Engineering, 2013)
Prosperous companies in the 21st century have come to know the necessity of intangible assets as an important factor to achieve sustainable competitive advantage and constant presence in the international markets. Hence, the purpose of this paper is to examine intangible assets and evaluate its relationship with export behaviour in terms of export intensity (Export-Sales Ratio) and export type (Permanent, Occasional & Periodical). The population under study includes all export firms during 2002 until 2010 in Yazd province, Iran. Research data were collected by questionnaire and in order to answer the research questions and testing hypotheses, MCDM techniques (i.e. AHP & TOPSIS) and statistical analysis (i.e. ANOVA) were utilized. According to the research results, human capital, relational capital, technological capital, corporate reputation, and structural capital placed as the first to the fifth significant factors respectively. Findings revealed that there is a significant difference between the permanent and occasional presence in the international markets regarding intangible assets; as the mean of intangible assets in the firms with permanent export is higher than the mean of intangible assets in the firms with occasional export. However, there is no significant difference between intangible assets and the export intensity.